2016
DOI: 10.21273/hortsci.51.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Growth and Leaf Nutrient Status of ‘Carpino’ Chrysanthemum on a Pecan Wood-amended Commercial Substrate

Abstract: Commercial production of pecan [Carya illinoinensis (Wangenh.) K. Koch.] generates significant woody biomass from hedge prunings with little economic value. Value-added uses could aid pecan growers, and one possible use is wood chips for potting substrates to lessen dependence on peatmoss, thereby aiding greenhouse growers. We evaluated vegetative growth and leaf nutrient responses of ‘Carpino’ garden chrysanthemum (Dendranthema ×grandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Given the extensive use of peat in chrysanthemum production, it is crucial to explore suitable substitutes to reduce peat usage and achieve sustainable horticultural practices while ensuring productivity and ornamental value. Some studies have shown that vermicompost and pecan wood chips can replace peat as a cultivation substrate for chrysanthemum growth [21,22]. However, the benefits of using rice husks and leaf mold as alternatives to peat in chrysanthemum cultivation remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Given the extensive use of peat in chrysanthemum production, it is crucial to explore suitable substitutes to reduce peat usage and achieve sustainable horticultural practices while ensuring productivity and ornamental value. Some studies have shown that vermicompost and pecan wood chips can replace peat as a cultivation substrate for chrysanthemum growth [21,22]. However, the benefits of using rice husks and leaf mold as alternatives to peat in chrysanthemum cultivation remain unknown.…”
Section: Introductionmentioning
confidence: 99%